Comparative analysis of ERP driven HRM practices: a case study on Kazi Farms Limited navigating through iDempiere system - Mizan, Marufa Binta (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.